2020
DOI: 10.1097/acm.0000000000003793
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Views on Implementing the Core EPAs: Recommendations From Student Leaders at the Core EPAs Pilot Institutions

Abstract: In 2014, the Association of American Medical Colleges recruited 10 institutions across the United States to pilot the 13 Core Entrustable Professional Activities for Entering Residency (Core EPAs). The goal was to establish a competency-based framework to prepare graduating medical students for the transition to residency. Within the Core EPAs pilot, medical students play an influential role in the development and implementation of EPA-related curricula. Student engagement was a priority for the Core EPAs inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…(Carraccio et al, 2002;Frank et al, 2010;McGaghie et al, 1978). In undergraduate programs, entrustment decisions are often also theoretical, reflecting an intention to trust or an decision on trustworthiness, rather that an actual entrustment decision (Brown et al, 2021;Geraghty et al, 2021;Postmes et al, 2021). This leaves the power of entrustment decisions underutilized and EPAs may subsequently become just educational objectives.…”
Section: Entrustment Decision Making Without Consequences For Clinica...mentioning
confidence: 99%
“…(Carraccio et al, 2002;Frank et al, 2010;McGaghie et al, 1978). In undergraduate programs, entrustment decisions are often also theoretical, reflecting an intention to trust or an decision on trustworthiness, rather that an actual entrustment decision (Brown et al, 2021;Geraghty et al, 2021;Postmes et al, 2021). This leaves the power of entrustment decisions underutilized and EPAs may subsequently become just educational objectives.…”
Section: Entrustment Decision Making Without Consequences For Clinica...mentioning
confidence: 99%
“…In a recent publication, medical students recommended against linking EPA assessments to grades on the basis that it would hinder with the developmental perspective of progression toward entrustment. 42 From a philosophical standpoint, we agree with this perspective and this was a significant driver toward our decision to decouple the WBAs from grades. However, in conversations with our student leaders, many admitted that the absence of direct ties to grades led to lower prioritization in requesting feedback provided.…”
Section: Discussionmentioning
confidence: 72%
“…Trainees found that asynchronous, individual testing provided psychological safety, and residency directors believed that the score reports could guide the development of individualized learning plans early in residency training. Psychological safety and targeted, individualized feedback are desirable outcomes consistent with other EPA-based studies [ 21 - 23 ].…”
Section: Discussionmentioning
confidence: 79%